Designing a Management Information System Prototype for a Philanthropic Organization: a Case Study of YAAB Orbit Yogya - Sita Dewi Kusumaningrum; Hari Setiaji; Wildan Maulana (Compiler, 2019)
Modern philanthropic organizations are responsible for the use of social resources. However, some of them are facing several managerial issues, including inadequate database management and lack of accountability. To support the documenting process and to improve the management of funds, these organizations need a computer-based information management. This qualitative action research using prototyping method aimed at designing a management information system for a philanthropic organization which focus on providing education access for disadvantaged students in Yogyakarta. The process of designing management information system in the case study was applying a prototyping method since not every organization including a philanthropic organization could explicitly define the information needed to support their business process. This prototype was designed based on organization’s requirements so that users can obtain any information needed easily. The management information system prototype could provide assistance for a philanthropic organization in managing and documenting all activities in the organization.